PERAN PIMPINAN DAN KOMITMEN PEGAWAI DALAM MENINGKATKAN PELAYANAN MASYARAKAT PADA KANTOR DESA MENINTING, BATU LAYAR - Vina Tamala Sari; Syaiful Amri; Sigit Ary Wijayanto (Kompeten: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
The high and low quality of services provided does not only depend on the performance of village officials as subordinates, but also their leaders, village officials are required to provide maximum service to the community and be able to answer demands from the community, both in terms of quality and quantity. This study aims to analyze the role of leadership and employee commitment in improving community services. The type of research conducted is qualitative research, with research informants namely the Secretary of Meninting Village, Head of Meninting Village Service, Head of TU & General Affairs of Meninting Village and three people from the community. Data collection using documentation techniques, observation and in-depth interviews. The data analysis used consisted of data collection, data reduction, data presentation, and drawing conclusions. The results showed that the Meninting Village Head implemented his role very well, namely as an interpersonal role, always giving examples, guiding, and creating good teamwork, informational role, namely seeking and providing important information for the organization and decisional role, namely being able to make good decisions for the organization. organizational progress that aims to improve employee performance in serving the community. The commitment of Meninting Village employees is not fully maximized because some employees have not complied with work discipline regulations so that it affects performance which means a decrease in service to the community but they are ready to work more for the organization by working continuously to maximize services and want to maintain their membership because of coordination and good demeanor among fellow employees